Psoriasis, psoriatic arthritis, and rheumatoid arthritis: Is all inflammation the same? - Coates, L; Fitzgerald, O; Helliwell, P; Paul, C (Elsevier, 2016)
Objectives To review the pathophysiology, co-morbidities, and therapeutic options for psoriasis, psoriatic arthritis and rheumatoid arthritis in order to further understand the similarities and differences in treatment paradigms in the management of each disease. New targets for individualized therapeutic decisions are also identified with the aim of improving therapeutic outcome and reducing toxicity. Search strategy Using the PubMed database, we searched literature published from 2000 to 2015 using combinations of the key words “psoriasis,” “psoriatic arthritis,” “rheumatoid arthritis,” “pathogenesis,” “immunomodulation,” and “treatment.” Inclusion and exclusion criteria This was a non-systematic review and there were no formal inclusion and exclusion criteria. Data extraction Abstracts identified in the search were screened for relevance and articles considered appropriate evaluated further. References within these selected articles were also screened. Information was extracted from 198 articles for inclusion in this report. Data synthesis There was no formal data synthesis. Articles were reviewed and summarized according to disease area (psoriasis, psoriatic arthritis, and rheumatoid arthritis). Headline results The pathophysiology of psoriasis, psoriatic arthritis, and rheumatoid arthritis involves chronic inflammation mediated by pro-inflammatory cytokines. Dysfunction in integrated signaling pathways affecting different constituents of the immune system result in varying clinical features in the three diseases. Co-morbidities, including cardiovascular disease, malignancies, and non-alcoholic fatty liver disease are increased. Increased understanding of the immunopathogenesis allowed development of targeted treatments; however, despite a variety of potentially predictive genetic, protein and cellular biomarkers, there is still significant unmet need in these three inflammatory disorders.